EXERCISE TOLERANCE TEST AS A SCREENING TOOL FOR CORONARY ARTERY DISEASE IN ASYMPTOMATIC ADULTS - Anwar, Wasif; Shahid, Rana; Sheikh, Nadeem Ahmed; Saif, Mohsin (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the screening efficacy of exercise tolerance test in the diagnosis of coronary artery disease in asymptomatic physically active adults. Study Design: Hospital-based cross-sectional validation study. Place and Duration of Study: Department of Medicine, Combined Military Hospital Mangla Cantonment, from Jan 2019 to Nov 2019. Methodology: Eight Hundred and Four patients fulfilling the inclusion criteria were included in study after obtaining informed written consent. All the enrolled subjects underwent an exercise tolerance test. Those subjects who had a normal exercise tolerance test were not assessed further and those who had an abnormal or inconclusive exercise tolerance test were referred to Armed Forces Institute of Cardiology/National Institute of Heart Diseases for coronary angiography. A database was maintained and used for further analysis. Results: Exercise tolerance test positivity is very low in asymptomatic young and active males, which was established to be 9% in our study. Similarly it was found that the positive predictive value of an abnormal exercise tolerance test result is also unacceptably low i.e. 18%. Conclusion: The diagnostic yield of exercise tolerance test remains low in view of a very high rate of false positive results, technical & procedural shortfalls and ethical constraints of subjecting asymptomatic persons to invasive and expensive coronary angiography.